120 nm wide band switchable fiber laser - Ahmad, Harith; Zulkifli, M.Z.; Latif, A.A.; Hassan, N.A.; Ghani, Z.A.; Harun, Sulaiman Wadi (Elsevier, 2010)
A novel method of producing switchable tunable output that spans the S-, C- and L-bands is presented. The achievable tuning range is about 120 nm. The design consists of a wide band SOA, 1 x 16 AWG and an optical selectable switch in a ring configuration. The measured average output powers for S-. C- and L-bands for different output wavelengths are -7.0 dBm, -6 dBm and -6.5 dBm respectively. The SMSR for these wavelengths is about 72 dB. (C) 2010 Elsevier BM. All rights reserved.